Analysis of Influencing Factor on Tapered Roller Bearing Vibration based on Poor Information - Xia Xintao; Liu Bin; Jiang Songjun; Xu Liang; Zhang Jixiang (Jixie chuandong)
The vibration of tapered roller bearings is affected by many factors,which belongs to the problem of poor information. Based on the theory of poor information system,by using a variety of correlation methods to analyze the influencing factors of different vibration values. The main influencing factors of each vibration value are analyzed by qualitative fusion,and then the main influencing factors of different vibration values are fused to obtain the main influencing factors of tapered roller bearing vibration. The experimental results show that the main factors affecting the bearing vibration under the measurement conditions are the roller base runout,the roller straightness,the roller diameter variation,the inner raceway roundness and the inner raceway verticality.